EFEKTIVITAS BELAJAR PROFIL PELAJAR PANCASILA DIMENSI BERNALAR KRITIS UNTUK PELAJARAN PPKN DENGAN MENGUNAKAN MODEL KOOPERATIF TIPE JIGSAW - Bundel Bundel; Totok Victor Didik Saputro (CV. ADIBA ASIHA AMIRA, 2025)
Learning that has been carried out so far has only used conventional methods that are not in accordance with the characteristics of students. Learning outcomes that have been carried out not effective in the child by because only the teacher is active in class, the students are passive. So that the low PPKN learning outcomes in class IV SDS Amkur Bengkayang. This study aims to analyze the effect of the jigsaw type Cooperative model on the profile of Pancasila students in the critical reasoning dimension of the 2024/2025 Academic Year, before and after using the jigsaw type cooperative learning model. The type of research used in this study is experimental research consisting of two cycles. This study uses PPKN learning outcome tests in the form of essays and groups. on the material of Pancasila as a life value The attitude of loving fellow human beings and their environment, and respecting diversity. The subjects of this study were 43 students of class IV of SDS Amkur Bengkayang, consisting of 22 males and 21 females. The results obtained in this study are an increase in PPKN learning outcomes in grade IV students of SDS Amkur Bengkayang. The increase in student learning outcomes is that in the pre-cycle, 32 students did not complete the course (80%), in cycle I, 11 students completed the course (20%), while in cycle II, 43 students did not complete the course, 21 students (9.33%) had met the KKM or it can be said that 22 students completed the course (90.67%). Thus, it can be concluded that the use of the jigsaw cooperative learning model can improve the learning outcomes of grade IV students of SDS Amkur Bengkayang through the jigsaw cooperative learning model